Design guidelines for on-site stormwater detention - Freire, Flávio Bentes; Souza, Ricardo Cesar Conrado de; Mannich, Michael (Ciência e Natura, 2021)
The city of Curitiba-PR has a municipal decree that establishes the criteria for the design of flood detention tanks. However, these guidelines do not guarantee minimum efficiency during operation, as it may vary depending on their base area, water depth and flow regulating orifice diameter. In this research, a design method was proposed, establishing some new criteria that relate impervious areas of the lots to the tank design parameters. The efficiency definition was established with the premise that the tanks should provide the return of flows from an impervious area to its pre-urbanization scenario. This reduction was established as 70% of the peak flow in the city of Curitiba-PR. Based on simulations of flow routing with the Puls Method, the optimum geometric characteristics (volume, area, water depth and orifice diameter) of the tanks were obtained to guarantee the decrease in the peak. Comparing the results obtained from the municipal legislation design, the new method provided n minimal efficiency and a decrease of 24% of the tank volume.